Intercultural Communicative Competence (ICC): What Should Indonesian EFL Teachers Have Related to ICC’s Elements? - Mas Muhammad Idris; Agus Widyantoro (Yayasan Visi Intan Permata, 2019)
In the twenty-first century life, the demand to become an intercultural speaker becomes very crucial. It is seen through the incremental important attention of having an intercultural communicative competence (ICC) which is seen as one of the main key competencies in global world-wide. This condition urges any teacher to master the ICC completely as to assist their students to become intercultural speakers in multicultural situations. However, this competence has not been noticed thoroughly by Indonesian EFL teachers since most of them are reluctant to develop their competence in term of integrating the elements of ICC into their teaching-learning process. Hence, this present article recommends a number of competencies related to ICC’s elements in which the Indonesian EFL teachers should have, namely, the linguistic, sociolinguistic, discourse, and intercultural competence which are considered able to aid the Indonesian EFL teachers in enhancing the students’ ICC.